2007
DOI: 10.1103/physrevc.76.044307
|View full text |Cite
|
Sign up to set email alerts
|

Spin-isospin nuclear response using the existing microscopic Skyrme functionals

Abstract: Our paper aims at providing an answer to the question whether one can reliably describe the properties of the most important spin-isospin nuclear excitations, by using the available nonrelativistic Skyrme energy functionals. Our method, which has been introduced in a previous publication devoted to the Isobaric Analog states, is the self-consistent Quasiparticle Random Phase Approximation (QRPA). The inclusion of pairing is instrumental for describing a number of experimentally measured spherical systems which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 57 publications
4
89
0
Order By: Relevance
“…However, this term of the residual interaction has been shown to be very small [122] in the case of the GTR; no further approximation is involved. The values reported in Table 2 are, however, calculated by dropping completely the spin-orbit contribution, both at HF and RPA level.…”
Section: Gamow-teller Statesmentioning
confidence: 99%
“…However, this term of the residual interaction has been shown to be very small [122] in the case of the GTR; no further approximation is involved. The values reported in Table 2 are, however, calculated by dropping completely the spin-orbit contribution, both at HF and RPA level.…”
Section: Gamow-teller Statesmentioning
confidence: 99%
“…In Ref. [62] it was shown that the lack of these time-odd terms can significantly alter the energy location of the GTR, which dominates the landscape in the (charge-exchange) 1 + channel. It also turned out that the GTR collectivity, which, as known, experimentally absorbs the 60% of the Ikeda-Fuji-Fujita sum rule, can be badly affected by relatively strong (negative) values of the C T 1 coupling constant, a fact which explained the peculiar behaviour of the SLy5 parametrization with respect to other Skyrme forces.…”
Section: B Unrestricted Skyrme Energy Density Functionalmentioning
confidence: 99%
“…Neglecting them leads to a breaking of consistency in terms of an incomplete implementation of the functional. For a more complete discussion refer to [62], where a comparison between predictions from the SLy4 force, fitted without that contribution ("type I" force), and the SLy5 set, which included it ("type II"), was considered; ambiguities related to the former type of force were pointed out. In particular, it was discussed that the contribution from the ↔ J 2 terms in computing the excited states can be more important than in the ground-state, with the result that standard fitting procedures, unable to capture some physics through the ground-state observables, can lead to poor results when computing collective excitations.…”
Section: B Unrestricted Skyrme Energy Density Functionalmentioning
confidence: 99%
“…One can see that the tensor correlations induces 3.6 MeV downward shift of the main peak in this nucleus. Also, part of the main peak strength is fragmented in the low-energy peaks and also a high-energy tail is formed at 06001-p. 3 around E=50MeV. Looking at the main peak we find that the main configuration is {π1h 9 2 ν1h 11 2 } (80 % and 64 % of the QRPA calculations with and without the tensor terms, respectively).…”
Section: Application To 126−130 CDmentioning
confidence: 99%
“…One of the successful tools for the studies of GT strength distributions is the quasiparticle random phase approximation (QRPA) with the self-consistent mean-field derived by the Skyrme interaction, see for example [1][2][3][4][5]. These QRPA calculations allow one to relate the properties of the ground states and excited states through the same energy density functional.…”
Section: Introductionmentioning
confidence: 99%